Dynamic filtration in baleen whales: recent discoveries and emerging trends - Werth, Alexander J.; Potvin, Jean (Frontiers in Marine Science, 2024)
Recent findings have greatly improved our understanding of mysticete oral filtration, and have upended the traditional view of baleen filtration as a simple process. Flow tank experiments, telemetric tag deployment on whales, and other lab and field methods continue to yield new data and ideas. These suggest that several mechanisms arose from ecological, morphological, and biomechanical adaptations facilitating the evolution of extreme body size in Mysticeti. Multiple lines of evidence strongly support a characterization of baleen filtration as a conceptually dynamic process, varying according to diverse intraoral locations and times of the filtration process, and to other prevailing conditions. We highlight these lines of evidence. First, baleen appears to work as a complex metafilter comprising multiple components with differing properties, including major and minor plates, eroded fringes, and whole baleen racks. Second, different whale species rely on varied ecological filtration modes ranging from slow skimming to high-speed lunging. Third, baleen filtration appears to be a highly dynamic and flow-dependent process, with porosity varying within a single rack and by flow direction, speed, and volume. Fourth, findings indicate that baleen (particularly of balaenid whales) functions not as a simple throughput sieve, but instead uses cross-flow or other tangential filtration.Fifth, the time course of baleen filtration, including rate of filter filling and clearing, appears more complex than formerly envisioned. Flow direction, and possibly plate and fringe orientation, appears to change during different stages of ram filtration and water expulsion. Sixth, baleen's flexibility and related biomechanical properties varies by location, leading to varying filtration conditions and outcomes. Seventh, the means of clearing/cleaning the baleen filter, whether by hydraulic, hydrodynamic, or mechanical methods, appears to vary by species and feeding type. Together, recent findings have greatly elucidated baleen filtration processes. Many aspects of baleen filtration may pertain to other biological filters; designers can apply several aspects to artificial filtration, both to better understand natural systems and to design and manufacture more effective synthetic filters. Understanding common versus unique features of varied filtration phenomena, both biological and artificial, will continue to aid scientific and technical understanding, enable fruitful interdisciplinary partnerships, and yield new filter designs.